Diverse rural caregivers for individuals with Alzheimer's disease or related dementias: analysis of health factors at the individual, interpersonal, and community level. (2nd January 2023) - McCarthy, Michael J.; Garcia, Y. Evie; Remiker, Mark; Hustead, Morgan Lee-Regalado; Bacon, Rachel; Williamson, Heather J.; Dunn, Dorothy J.; Baldwin, Julie
Abstract: Objectives: Approximately 6.2 million Americans aged 65 or older have Alzheimer's disease or related dementias (ADRD). Unpaid family members and friends provide the bulk of caregiving for these individuals. Caregiving in rural areas adds unique challenges, particularly for ethnically/racially diverse caregivers. This study provides a profile of diverse, rural ADRD caregivers with an emphasis on multi-level factors that influence physical and mental health. Methods: A cross-sectional survey was conducted with 156 diverse rural ADRD caregivers. Results: 65% of participants identified as White/Non-Hispanic (WNH; n = 101) and 35% identified as ethnically/racially diverse (ERD; n = 55). The majority of participants reported economic deprivation. More ERD caregivers were uninsured and had at least one chronic health condition. Higher proportions of ERD caregivers smoked cigarettes, consumed alcohol regularly, and had not seen or talked to a doctor in the previous year. There were no ethnic/racial group differences in stress, anxiety, depressive symptoms, subjective health, or sleep quality. Conclusion: Rural caregivers, regardless of ethnicity/race, may benefit from extra supports in order to maintain optimal health. Further research is needed to disentangle the complex relationship between culture, caregiving, and health.